Implementasi Core Tax Administration System (CTAS) dalam Pelaporan Pajak: Studi Kasus pada PT X - Dilla Salsabilla; Heriyanto Heriyanto (CV Widina Media Utama, 2026)
ABSTRACTThe implementation of coretax represents a key component of the digital transformation of tax administration aimed at improving the effectiveness and efficiency of tax reporting. This study aims to find out how Coretax is implemented in tax reporting at PT X, the challenges faced during implementation, and the effectiveness of Coretax in improving accuracy and saving time in the company's tax reporting. This study employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation. The findings indicate that the implementation of coretax has integrated tax administration and reporting into a single system, resulting in a more streamlined reporting process. From a technology perspective, Coretax makes tax administration easier and improves reporting efficiency, even though there are still technical issues like system errors, difficulties in access, and tax data not appearing in the tax return. From an organizational perspective, the implementation of Coretax is supported by internal company coordination, human resource readiness, and the process of users adapting to the new system. From an environmental aspect, the implementation of coretax is influenced by government policies related to digital-based tax administration reforms and the support of the Directorate General of Taxes in the system implementation process. The research conclusion shows that the implementation of coretax at PT X has generally aligned with the Technology Organization Environment (TOE) theory because it involves the interconnection between technological, organizational, and environmental aspects in applying the digital tax system. ABSTRAKCore Tax Administration System (CTAS) dikembangkan sebagai bagian dari transformasi digital administrasi perpajakan yang bertujuan mengintegrasikan berbagai layanan perpajakan sehingga proses pelaporan pajak menjadi lebih efektif dan efisien. Penelitian ini berfokus pada analisis implementasi coretax dalam proses pelaporan pajak di PT X, termasuk mengidentifikasi berbagai hambatan yang dihadapi serta mengevaluasi efektivitas penerapannya. Penelitian menggunakan metode kualitatif dengan pendekatan deskriptif. Data penelitian dikumpulkan melalui teknik wawancara, observasi, dan dokumentasi. Temuan penelitian mengindikasikan proses administrasi dan pelaporan pajak ke dalam satu sistem yang lebih terstruktur. Ditinjau dari aspek teknologi, coretax memberikan kemudahan dalam pengelolaan administrasi perpajakan sekaligus meningkatkan efisiensi pelaporan. Di sisi lain, penerapan sistem masih menghadapi berbagai hambatan teknis, antara lain munculnya system error, kendala akses, serta belum sinkronnya sebagian data perpajakan pada Surat Pemberitahuan (SPT). Dari aspek organisasi, implementasi coretax didukung oleh koordinasi internal perusahaan, kesiapan sumber daya manusia, serta proses adaptasi pengguna terhadap sistem baru. Dari aspek lingkungan, implementasi coretax dipengaruhi oleh kebijakan pemerintah terkait reformasi administrasi perpajakan berbasis digital dan dukungan Direktorat Jenderal Pajak dalam proses implementasi sistem. Secara keseluruhan, implementasi coretax di PT X menunjukkan kesesuaian dengan kerangka Technology Organization Environment (TOE), yang tercermin dari keterkaitan faktor teknologi, organisasi, dan lingkungan dalam proses implementasinya.